2017
DOI: 10.1016/j.celrep.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Massive and Reproducible Production of Liver Buds Entirely from Human Pluripotent Stem Cells

Abstract: Organoid technology provides a revolutionary paradigm toward therapy but has yet to be applied in humans, mainly because of reproducibility and scalability challenges. Here, we overcome these limitations by evolving a scalable organ bud production platform entirely from human induced pluripotent stem cells (iPSC). By conducting massive "reverse" screen experiments, we identified three progenitor populations that can effectively generate liver buds in a highly reproducible manner: hepatic endoderm, endothelium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
323
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(354 citation statements)
references
References 28 publications
(33 reference statements)
0
323
0
2
Order By: Relevance
“…Specifically, they have used iPSC‐derived hepatic endoderm, endothelium, and septum mesenchyme, which enables self‐condensation, hepatic maturation, and vascularization of a successful in vivo transplant. [ 54 ] In this context, we aim to use an iPSC‐derived hepatocyte, which is one of the suitable substitutes of HepG2/C3A, hepatic sinusoidal endothelial cells, hepatic stellate cells, and Kupffer cells or immune cells, as well as primary cells, for hepatic function and tissue‐engineered grafts.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, they have used iPSC‐derived hepatic endoderm, endothelium, and septum mesenchyme, which enables self‐condensation, hepatic maturation, and vascularization of a successful in vivo transplant. [ 54 ] In this context, we aim to use an iPSC‐derived hepatocyte, which is one of the suitable substitutes of HepG2/C3A, hepatic sinusoidal endothelial cells, hepatic stellate cells, and Kupffer cells or immune cells, as well as primary cells, for hepatic function and tissue‐engineered grafts.…”
Section: Resultsmentioning
confidence: 99%
“…(c) Current-generation hPSC-derived brain organoids possess some key features of early brain development, but various questions remain. hPSC, human pluripotent stem cell hPSC-derived liver precursors and then, at an intermediate step of differentiation, introduced defined numbers of generic endothelial cells (e.g., human umbilical vein endothelial cells) and generic mesenchymal cells to produce threedimensional cultures (Takebe et al, 2013;Takebe et al, 2017). Incorporation of endothelial and mesenchymal cells is an important step to engineer increasingly sophisticated organ simulacra.…”
Section: Identifying the Target: Benchmarking Hpsc-derived Cell Typesmentioning
confidence: 99%
“…Three-dimensional (3D) cultures of liver tissues, based on the spontaneous formation of organoids from a coculture of different cell types, have unequivocally shown that a 3D configuration maintains more efficiently the function and viability of liver cells (Takebe et al, 2017). Indeed, to date, all approaches, including organ decellularization and recellularization, have failed to deliver functional models.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to date, all approaches, including organ decellularization and recellularization, have failed to deliver functional models. Three-dimensional (3D) cultures of liver tissues, based on the spontaneous formation of organoids from a coculture of different cell types, have unequivocally shown that a 3D configuration maintains more efficiently the function and viability of liver cells (Takebe et al, 2017). An alternative liver modeling strategy is to develop both healthy and disease liver-on-chip models.…”
Section: Introductionmentioning
confidence: 99%